Causes and Consequences of Peri-Urban Land Conflicts in Ethiopia: The Case of Mekelle City - Araya Negash; Girma Birhanu (Baltic Journal of Real Estate Economics and Construction Management)
In Ethiopia, like in other developing countries, land conflicts in urban fringes are usually subject to severe disputes. Different land tenure and administration systems may clash as land use converted from rural to urban status, resulting in disagreements, contestations, and occasional violence. Nevertheless, the specific reasons for peri-urban land conflict are not well understood in developing countries so far because of the political use of regularizing land tenure and the control exercised by a corporatist system of the government. Hence, accordingly, this paper explores the causes and consequences of peri-urban land conflicts in Mekelle City: Enderta district. A case study was used to answer the research question, while questionnaire and document analysis were the main sources of primary and secondary data. According to the research’s findings, overlapping legal and governance frameworks, a variety of property rights claims, local power dynamics, and self-serving individual interests are the main drivers of peri-urban land conflicts. Moreover, lowering tax revenue for the state or municipality, raising expenses, impeding investment, and causing conflict were the consequences of peri-urban land conflicts.